Potential of agro waste-derived adsorbent material for colour removal - Daud, Zawawi; Nasir, Nazlizan; Abdul Kadir, Aeslina; Abdul Latiff, Ab Aziz; Ridzuan, Mohd Baharudin; Awang, Halizah; Abdul Halim, Azhar (Trans Tech Publication, 2018)
The potential of Empty Fruit Bunch obtained from palm oil tree as a low-cost adsorbent is a sustainable approach in wastewater treatment. The objective this study to investigate the capability of EFB for removal colour from natural rubber wastewater as well as the influence of adsorbent dosage, pH, shaking speed and contact time. The results of the analysis show that all selected factors exhibit significant effect on removal of colour. Maximum removal (87.1%) for colour was achieved at 3.5 g of adsorbent dosage, pH 7, 150 rpm of shaking speed, 120 min of contact time. The Langmuir isotherm (R2 = 0.9913) described colour adsorption slightly better than the Freundlich isotherm (R2 = 0.9805), suggesting a monolayer adsorption behavior of the adsorption processes.